Research on the construction of supportability index of aviation equipment system of systems. Issue 2 (January 2021) - Ding, Gang; Cui, Li-Jie; Wang, Li-Yong; Hu, Rong; Qian, Guang
Abstract: According to the characteristics of the air force operation under the condition of informationization, the concept, connotation and characteristics of the supportability of the AESos(Aviation equipment system of systems) based on task are defined. Based on the supportability logical control relation of the AESos, the capability requirements of the system to different levels are defined, and the requirement of the system support capability is described in particular. Secondly, following the idea of model-capability-index, and on the basis of constructing the supportability index system of AESos, the paper puts forward three system-level indexes to evaluate the supportability of the AESos, which are the intact rate of the AESos, the availability of the AESos and the mission continuity probability of the AESos.Finally, the definition and calculation formula of the three system-level indexes are given, which can lay a foundation for modeling and analyzing the supportability of the AESos. It provides support for the evaluation, control, overall planning and optimization of maintenance support capability of modern AESos.